Shear behaviour of infra lightweight concrete (ILC) without stirrups. (November 2022) - Elshahawi, Mahmoud; Hückler, Alex; Schlaich, Mike
Abstract: ILC stands for "Infra" Lightweight Concrete, a versatile construction material that contributes significantly to building sustainability and opens up innovative architectural prospects. The prefix "infra" reflects a level of lightness that falls below the range of the structural LC in international standards. The novelty of ILC arises from combining such lightness (dry density ≤ 800 kg/m 3 ) with both moderate strength and good heat insulative characteristics, rendering its application in monolithic cross sections without additional insulation layers feasible. This implies that complex multilayer façade systems including highly insulative materials can be substituted with a single layer of ILC, resulting in substantial improvements in terms of planning and construction simplicity, energy savings and recyclability. Recently, ILC has received great research attention, allowing for a better understanding of its physical and mechanical properties, which resulted in the successful construction of several ILC buildings in Germany. However, the structural behaviour of ILC has not been completely investigated and some structural concerns remain unanswered. This paper focusses on the diagonal cracking of ILC without web reinforcement as part of a comprehensive study into understanding the overall shear behaviour. 26 simply supported beams were tested until failure in 4-point bending configuration tests in order to study the role the concrete strength, the longitudinal reinforcement ratio and the a/d ratio play in the diagonal cracking of ILC. It was found that the excessive shrinkage of ILC significantly reduces the diagonal cracking load and results in rather wider cracks. Therefore, a design approach has been developed, where the excessive shrinkage impact was processed by reducing the tensile strength of ILC based on the shrinkage strain value. The diagonal cracking load seemed to be connected to the reduced tensile strength and the depth of the compressed zone, with no influence of aggregate interlocking or dowel action.